Two-fund separation in dynamic general equilibrium - Karl Schmedders (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
This paper examines the two-fund separation paradigm in the context of an infinite-horizon general equilibrium model with dynamically complete markets and heterogeneous consumers with time- and state-separable utility functions. With the exception of the dynamic structure, we maintain the assumptions of the classical static models that exhibit two-fund separation with a riskless security. Agents have equi-cautious HARA utility functions. In addition to a security with state-independent payoffs, agents can trade a collection of assets with dividends following a time-homogeneousMarkov process. We make no further assumptions about the distribution of asset dividends, returns, or prices. If the riskless security in the economy is a consol then agents' portfolios exhibit two-fund separation. However, if agents can trade only a one-period bond, this result no longer holds. The underlying intuition is that general equilibrium restrictions lead to interest rate fluctuations that destroy the optimality of two-fund separation in economies with a one-period bond and result in different equilibrium portfolios.
Keywords: D53; G11; G12; 330; Portfolio separation; dynamically complete markets; consol; oneperiod bond; interest rate fluctuation; reinvestment risk